Impact of Recipient Vein Selection on Venous Patency and Free Flap Survival in 652 Head and Neck Reconstructions - Choi, Jong Woo; Kim, Young Chul; Jeon, Dong Neok; Jeong, Woo Shik; Koh, Kyung S.; Oh, Tae Suk; Eom, Jin Sup; Kim, Eun Key; Hong, Joon Pio; Suh, Hyunsuk Peter (Journal of Reconstructive Microsurgery, 2020)
Background This study was conducted to evaluate the impact of choosing a particular recipient venous system on venous patency and flap survival in 652 head and neck free flap reconstructions.Methods A retrospective review was performed. Patient factors investigated included: age, sex, type of flap, tumor location, history of radiation, presence of previous neck dissection, tumor stage, and any underlying disease. Data related with recipient vein including the number of anastomosis, the repair technique, the type of recipient vein, and the configuration of selected venous system were examined. The impact of patient factors and parameters related with recipient vein on the venous patency and flap survival were analyzed using bivariate and multivariate analyses.Results Of 652 free flaps, 36 flaps (5.5%) were re-explored due to venous congestion and 28 flaps (77.8%) were salvaged. The overall survival rate of total free flaps was 98.8%. The type of recipient venous system was found to be an insignificant factor with respect to venous congestion and flap survival in multivariate analysis. A history of radiation treatments was the only factor associated with a higher risk of venous compromise (odds ratio [OR] = 13.138, p < 0.001) and a lower rate of flap survival (OR = 20.182, p = 0.002).Conclusion The selection of recipient venous systems has no impact on venous patency and flap survival. History of radiation treatment was the only factor associated with venous congestion and flap failure. Since no single method can ensure a successful reconstructive result, selecting the optimal recipient vein should be based on individual patient factors and the surgeon's experience.
Keywords: head and neck reconstruction; recipient vein; flap viability